INFLUENCE OF ACCESS DETERMINANTS ON SELF-REFERRALS AMONG PREGNANT WOMEN SEEKING DELIVERY SERVICE IN COAST GENERAL REFERRAL AND TEACHING HOSPITAL MOMBASA, KENYA - Kivuva , Elizabeth; Njoroge, Kezia; Tenambergen , Wanja (Global Journal of Health Sciences, 2021)
Purpose: The purpose of this study was to establish influence of access determinants on self-referrals among pregnant women seeking delivery service in Coast General Referral and Teaching Hospital (CGTRH). Methodology: The study adopted a descriptive cross-sectional research. The study target population was all pregnant women seeking delivery services in coast general teaching and referral hospital at the maternity unit. Therefore, 6,420 formed the study population as it is from this sampling frame that a sample of mothers was obtained. A sample of 376 pregnant women was obtained. Systematic random sampling was used to select the pregnant women to be included in the sample. Data was collected using a structured questionnaire. The data collected were cleaned and coded, quantified and analyzed quantitatively. Quantitative data were analyzed using IBM SPSS where descriptive and inferential statistics were used to capture the data in order to understand the pattern and nature of relationships. Univariate analysis was done using descriptive statistics (frequencies and percentages,) in order to summarize the data, and the results were presented using charts, graph and tables. Results: The findings revealed a significant relationship between the operating hours of CGTRH and self-referrals to the facility. The results indicated that pregnant women who indicated the 24 hours operating nature of CGTRH as their reason for seeking services at the facility were 2 times more likely to make self-referrals compared to those who disagreed that they sought services at the facility because the facility is open 24 hours in a day. A multivariable logistic regression analysis at a significance level of 0.05 further indicated that the operating hours of CGTRH had a significant influence on self-referrals pregnant women seeking delivery services at the facility. Unique contribution to theory, practice and policy: The study recommended that The Mombasa county department of health should find ways of ensuring that primary health facilities in the county are open for 24 hours in a day to attract more pregnant women seeking delivery services at the facilities and thus minimize the number of pregnant women seeking delivery services directly from the Coast General Teaching and Referral Hospital.